2020
DOI: 10.1111/1759-7714.13459
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐100 functions as a tumor suppressor in non‐small cell lung cancer via regulating epithelial‐mesenchymal transition and Wnt/β‐catenin by targeting HOXA1

Abstract: Background: Non-small cell lung cancer (NSCLC) is a leading subtype in lung cancer, with high morbidities and mortalities worldwide. microRNA (miRNA) has appeared to play indispensable roles in a variety of solid carcinomas. The current study focused on the functions of miR-100 in NSCLC. Methods: qRT-PCR was performed to detect miR-100 and HOXA1 expressions in NSCLC tissues and cells. MTT and transwell assays were used to determine the functions of miR-100 in NSCLC cell proliferation, invasion and migration ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…HOXA1 encodes a DNA-binding transcription factor that regulates gene expression, morphogenesis, and differentiation. Previous studies have reported that HOXA1 contributes to cancer pathogenesis and progression, immunosuppressive activity of myeloid-derived suppressor cells, and therapeutic response ( 54 60 ). The results of the rescue assays indicated that LINC00958 promotes lung cancer progression by regulating the transcriptional activity of HOXA1.…”
Section: Discussionmentioning
confidence: 99%
“…HOXA1 encodes a DNA-binding transcription factor that regulates gene expression, morphogenesis, and differentiation. Previous studies have reported that HOXA1 contributes to cancer pathogenesis and progression, immunosuppressive activity of myeloid-derived suppressor cells, and therapeutic response ( 54 60 ). The results of the rescue assays indicated that LINC00958 promotes lung cancer progression by regulating the transcriptional activity of HOXA1.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we identified significant downregulation of miR-100-5p in the BALF-derived exosomes from COPD patients as compared to healthy smokers. Functionally, miR-100 is linked to the regulation of epithelial–mesenchymal transition (EMT), apoptosis, and inflammation [ 51 , 52 ]. Furthermore, Akbas and colleagues have demonstrated downregulation of miR-100-5p in the serum of COPD patients when compared to healthy smokers, which is in accordance with our study results [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we identified significant downregulation of miR-100-5p in the BALF-derived exosomes from COPD patients as compared to healthy smokers. Functionally, miR-100 has been linked to the regulation of epithelial-mesenchymal transition (EMT), apoptosis and inflammation (54, 55). Furthermore, Akbas and colleagues have demonstrated downregulation of miR-100-5p in the serum of COPD patients when compared to healthy smokers, which is in accordance to our study results (56).…”
Section: Discussionmentioning
confidence: 99%